PREDICTIVE FACTORS FOR MORTALITY FROM DELTA VARIANT OF SARS-COV-2 IN REPUBLIC OF NORTH MACEDONIA - Kochinski, Dragan; Velikj Stefanovska, Vesna; Popovska Kljuseva, Svetlana; Memeti, Shaban (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
In 2019, Wuhan registered an epidemic of a severe form of pneumonia. On January 7, 2020, the pathogen was identified as SARS-CoV-2. COVID-19 causes acute and fatal disease with an average mortality rate of 2%. Based on evidences, risk factors include age, underlying health conditions, vaccination status, and immune response. Five variants of concern have been identified by WHO. The Delta variant was first reported in India in late 2020.  The research aimed to analyze the predictive role of gender, number and type of comorbidities, hospitalization and vaccination status for mortality from Delta variant of SARS-CoV-2 in the Republic of North Macedonia. The research was a analitical cross-sectional study that included 56,030 cases and 2,292 deaths and elaborated the mortality from Delta variant of SARS-CoV-2 in the Republic of North Macedonia during the period June-November 2021. The analysis showed that the male gender (OR=1.30; 95% CI=1.20-1.42), the age â‰¥60 (OR=14.13; 95% CI=12.71-15.72), the positive comorbidity status (OR=13.69; 95% CI=12.25-15.29), and hospitalization (OR=208.1; 95% CI=178.6-242.5) significantly positively associated with death from Delta variant. Complete vaccination and/or booster dose had significant protective role reducing the probability for hospitalization and death from Delta variant for 38% and 47% respectively.  Male patients, older age and comorbidities positively associated with death from the Delta variant of SARS-CoV-2. The findings of this study can be utilized to compare mortality rates among different variants of SARS-CoV-2. Keywords: Delta SARS-CoV-2, mortality, hospitalization, vaccination, comorbidity, age